Reform of Linux operating system teaching integrating OBE concept for new engineering - Yu Jian (ITM Web of Conferences)
The "New Engineering" has put forward new requirements for the teaching of engineering courses such as computer science and technology, and Internet of Things engineering. Reform the entire teaching process of the Linux operating system course based on the OBE concept for the integration of new engineering disciplines, organically combining basic commands of the Linux operating system, network server configuration, Shell script programming, and Python language programming, integrating comprehensive examples of information security and the Internet of Things, and exploring the application-oriented engineering talent training mode for Linux operating system operation and development under the background of new engineering disciplines. The teaching performance of this course has been evaluated as excellent for three consecutive semesters, indicating that the teaching reform of the course has achieved the expected goals.